Beerhouses, brothels and bobbies : Policing by consent in Huddersfield and the Huddersfield district in the mid-nineteenth century - Taylor, David; Project Muse. (Huddersfield : University of Huddersfield Press, 2016)
Professor David Taylor has established a fine reputation for his books and articles on the history of policing in England. This new book on Huddersfield policing looks at the mid-nineteenth century and issues facing the local area in relation to policing a centre of West Riding textile production.
Description based on print version record.
Keywords: Police; Regional and national history; Humanities; History; European history; British and Irish history; Police -- England -- West Riding of Yorkshire -- History -- 19th century; Police -- England -- Huddersfield -- History -- 19th century; England -- West Riding of Yorkshire; England -- Huddersfield; History; Electronic book; Electronic books